Integrin β1 regulates leiomyoma cytoskeletal integrity and growth - Malik, Minnie (2012)
Uterine leiomyomas are characterized by an excessive extracellular matrix, increased mechanical stress, and increased active RhoA. Previously, we observed that mechanical signaling was attenuated in leiomyoma, but the mechanisms responsible remain unclear. Integrins, especially integrin β1, are transmembrane adhesion receptors that couple extracellular matrix stresses to the intracellular cytoskeleton to influence cell proliferation and differentiation. Here we characterized integrin and laminin to signaling in leiomyoma cells. We observed a 2.25 ± 0.32 fold increased expression of integrin β1 in leiomyoma cells, compared to myometrial cells. Antibody-mediated inhibition of integrin β1 led to significant growth inhibition in leiomyoma cells and a loss of cytoskeletal integrity. Specifically, polymerization of actin filaments and formation of focal adhesions were reduced by inhibition of integrin p1. Inhibition of integrin β1 in leiomyoma cells led to 0.81 ± 0.02 fold decrease in active RhoA, and resembled levels found in serum-starved cells. Likewise, inhibition of integrin β1 was accompanied by a decrease in phospho-ERK. Compared to myometrial cells, leiomyoma cells demonstrated increased expression of integrin α6 subunit to laminin receptor (1.91 ± 0.11 fold), and increased expression of laminin 5α (1.52±0.02), laminin 5β (3.06±0.92), and laminin 5γ (1.66 ± 0.06). Of note, leiomyoma cells grown on laminin matrix appear to realign themselves. Taken together, the findings reveal that the attenuated mechanical signaling in leiomyoma cells is accompanied by an increased expression and a dependence on integrin β1 signaling in leiomyoma cells, compared to myometrial cells.